Dynamical properties about ultrasonic vibration assisted drilling of TiBw/TC4 composite. (March 2021) - Feng, Yong; Wang, Haoxiang; Zhang, Min; Zhu, Zihao; Wang, Xiaoyu; Jia, Binhui; Jia, Xiaolin
TiBw / TC4 composite material was used as the machining object of Ultrasonic vibration assisted drilling (UVAD), the single directional three-degree-of-freedom dynamical system model was established. The dynamic signal test and analysis system was used for modal experiment to identify the parameters in the model. Under the condition of dry cutting, the drilling axial force and tool vibration in the drilling process are studied. The results showed that the maximum values of the predicted and measured axial drilling force were 412.5N and 439.6N respectively, and the error rate was 6.165%, which verified the reliability of the predicted axial drilling force model. For cutting tools, the average amplitudes of simulated vibration and measured vibration were 0.1124mm and 0.1151mm respectively, with a difference of 2.402%, and the overall trends were the same, which verifies the reliability of the dynamical model. Finally, the stability of drilling process was analyzed, and the frequency and amplitude of ultrasonic vibration were analyzed. The results show that in order to expand the unconditional stability region, it is more efficient to increase the amplitude than to increase the frequency.